2018
DOI: 10.1002/jbio.201700342
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared bone densitometry: A feasibility study on distal radius measurement

Abstract: Osteoporosis, defined as decreased bone mineral density (BMD), poses patients in dangers for fracture risk and has become a major public health problem worldwide because of is associated morbidity, mortality and costs. Without doubt, early detection and timely intervention are important to successfully manage osteoporosis and its associated complications. The dual-energy x-ray absorptiometry (DXA) is the most popular and standard method to measure BMD. However, limitations including radiation exposure and avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…7 seemingly contradict those reported by Chung et al. 14 Those authors demonstrated that the transmitted light intensity and aBMD are strongly correlated in the measurement of the ultradistal radius using an 850 nm wavelength light. However, in our results, the aBMD estimated only from transmitted light does not show a high coefficient of determination.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…7 seemingly contradict those reported by Chung et al. 14 Those authors demonstrated that the transmitted light intensity and aBMD are strongly correlated in the measurement of the ultradistal radius using an 850 nm wavelength light. However, in our results, the aBMD estimated only from transmitted light does not show a high coefficient of determination.…”
Section: Discussionmentioning
confidence: 70%
“…reported a correlation between near-infrared light transmittance and aBMD in the ultradistal radius, but they were concerned about the bias from soft tissue. 14 We previously reported that the slope of the intensity distribution formed by diffuse reflected light correlates with BMD but showed nonlinear variation with skin thickness and BMD. 13 …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Scientists have proven that the morphological parameters of the biological material are extremely informative in the course of diagnostic research, in particular, to determine in the course of forensic examination the species, sex, time of death and burial in both animal and human medicine (Shanbhogue et al, 2015;Chung et al, 2018). The skeleton is the most informative object for these tasks, because changes in the bones persist for a long time, and soft tissues decay quickly.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of their investigation revealed a robust correlation between the optical attenuation values and BMD measurements. This suggests that the NIR-based optical attenuation technique has the potential to serve as a valuable indicator of bone density, as assessed by DXA [19] .…”
Section: Introductionmentioning
confidence: 99%